Using Inquiry Based Learning to Improve Students Speaking Skills - Wahono, Suparwoto Sapto; Zahro, Ira Hamida Nurul (Journal of Language Intelligence and Culture, 2021)
English is one of the existing languages in this world. Speaking is one of the important skills in English. A priority for many second language or foreign language learners is the mastery of speaking. Speaking is one of the indicators that someone understands English. As a foreign language, English tends to be difficult to be learnt by foreign language learners. The researcher aimed to find out if the use of inquiry-based learning method can improve the students’ speaking skill at the tenth-grade students of vocational high school. This research used classroom action research (CAR). The cycles of this research were planning, acting, observing, and reflecting. The method used in collecting the data was a test. The research result of students’ pre test was 66.6. Meanwhile the students’ post test result was 72.2. In conclusion inquiry based learning method improved speaking skill at the tenth grade students of vocational high school.